TRADISI MENDEM BUNGA PADA UPACARA PUJAWALI PURA DALEM PUCAK DESA PAKRAMAN TISTA BAKTISERAGA - Ketut Agus Nova (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
The background of the Mendem Bunga tradition procession is because every pujawali ceremony held at Purnama Kapat at Dalem Pucak Temple, Tista Baktiseraga Traditional Village is still carried out at the intermediate level. Therefore, as a complement to the ceremony, it is added with flower cultivation. As for the series of Mendem Bunga traditions, namely: 1) Adult Ngagem and preparation of yadnya facilities, 2) Mepiuning to Pulaki Temple and Ulun Danau Temple, 3) Performing a rice tensioning ceremony, 4) Performing a fresh preservation ceremony, 5) Performing a kneading ceremony / lowering Ida Bhatara, 6) Making and presenting Canang Gebogan, and followed by carrying Canang Gebogan around the temple three times brought by unmarried young people, 7) Mendem Sekar/flowers, where previously pendem flowers are strung together in the form of Canang Gebogan and then predicated or purified. The hole where the sekar was placed was previously removed after that the sekar was buried or planted in a hole with a young coconut base. After the sekar procession is complete, then krama worships in front of the sekar hole, then the hole is closed, 8) Performing a prayer ceremony together